Evaluasi Efektivitas Sistem Green Water pada Pendederan Ikan Nila di Laboratorium Budidaya Perikanan Universitas Lampung - Reynaldo Reynaldo; David Surya Atmaja; Hilma Putri Fidyandini (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This study aims to evaluate the effectiveness of the green water system in the nursery phase of Nile tilapia Oreochromis niloticus by observing growth performance, water quality, and survival rate. The experiment was conducted for 21 days using 450-liter circular tanks with two treatments: green water and clear water systems. The green water system was established by adding plankton starter to stimulate algal growth, while the clear water system used clean water with routine siphoning. Observations included absolute length, absolute weight, water quality parameters pH, temperature, dissolved oxygen, nitrite, and phosphate, and survival rate. The results indicate that the green water system provided superior nursery performance compared to clear water. Tilapia seeds reared in green water exhibited higher growth in length and weight, more stable water quality, and a greater survival rate 90% than those in the clear water system 80%. These improvements are attributed to the presence of microalgae, which serve as natural feed as well as bioremediation agents that reduce ammonia, nitrite, and phosphate toxicity. Therefore, the green water system proves to be more effective, economical, and environmentally friendly for tilapia nursery culture compared to the clear water system.